Encyclopedia of political communication - Kaid, Lynda Lee; Holtz-Bacha, Christina (Gale virtual reference library, 2008)
Discusses the major theoretical approaches to the field, including direct and limited effects theories, agenda-setting theories, sociological theories, framing and priming theories, and other past and present conceptualizations. Focuses on important political messages such as political speeches, televised political advertising, political posters and print advertising, televised political debates, and Internet sites.